2014
DOI: 10.7567/jjap.53.08lb01
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of state transition of a defect causing random-telegraph-noise-induced fluctuation in stress-induced leakage current of SiO2films

Abstract: Dynamic fluctuation in stress-induced leakage current, called V-SILC, which is one of the causes of erratic bits in flash memory, was investigated. This investigation showed that V-SILC is attributed to random telegraph noise, which is associated with a state transition of a single defect. To analyze the mechanism of the state transition, dependences of state-transition probabilities on gate current and temperature were investigated. These dependences indicate that the state transitions are caused by current i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is well-established that these processes in dielectrics like SiO 2 can lead to the formation of metallic weak links that act as paths of low resistance for I leak thus reducing the breakdown voltage of the dielectric. 46,47 The same effects, however, can be achieved not only by applying a V G *, but also by injecting a high current through the dielectric. This process known as stress-induced leakage current (SILC) has been studied for metal-oxide-semiconductor field-effect transistors down to low temperature, where it has been reported that SILC manifests through fluctuations in I leak occurring over periods of few seconds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that these processes in dielectrics like SiO 2 can lead to the formation of metallic weak links that act as paths of low resistance for I leak thus reducing the breakdown voltage of the dielectric. 46,47 The same effects, however, can be achieved not only by applying a V G *, but also by injecting a high current through the dielectric. This process known as stress-induced leakage current (SILC) has been studied for metal-oxide-semiconductor field-effect transistors down to low temperature, where it has been reported that SILC manifests through fluctuations in I leak occurring over periods of few seconds.…”
Section: Resultsmentioning
confidence: 99%
“…We attribute the fluctuations in I leak and I c to electromigration and/or diffusion processes of atomic species that occur in the SiO 2 /Si substrate under an applied V G * . It is well-established that these processes in dielectrics like SiO 2 can lead to the formation of metallic weak links that act as paths of low resistance for I leak thus reducing the breakdown voltage of the dielectric. , …”
Section: Resultsmentioning
confidence: 99%
“…The tunneling ∆n model for 1/f noise in MOS transistors, which was originally suggested in [85], has been followed up widely [47,48,49,50,51,52,53,54,55,56,72,74,80,82,83,87,89,91,95,101,103,106,107,110,124,126,127,128,136,137,138,139,140,141,142,143,144,145]. It assumes that some charge carriers are trapped in the depth of the gate oxide.…”
Section: Tunneling Modelmentioning
confidence: 99%